Overall Equipment Effectiveness on Package Boiler Equipment and Preventive Maintenance Strategies Optimisation at Fertiliser Plant - Zubir, Awal Aflizal; Syahriza; Meutia Fadilla; Alifia Nadita (Jurnal Rekayasa Teknologi Nusa Putra, 2025)
One of the factors that requires more attention for the success of an industry is a smooth production process. PT XYZ is a company engaged in urea fertiliser and other chemical components. In its production process, the company needs steam as a primary resource, which is used both as a raw material for production and as an energy source. The problem the company faced during production is boiler downtime, resulting the lack of steam production generated. This study aims to calculate the boiler's effectiveness level using Overall Equipment Effectiveness (OEE) and to identify the risks of failure that occur in the boiler using Failure Mode and Effects Analysis (FMEA). Additionally, this study identifies the implementation of Total Productive Maintenance (TPM) within the company. Based on the OEE calculations, the boiler's effectiveness rate stands at 79.26%. These results indicate that the boiler's effectiveness has not met the international standards. The FMEA analysis reveals eight critical risks in the boiler, categorised as top priorities for maintenance. Improvements in OEE can be achieved by implementing one of the TPM pillars, which is preventive maintenance.